1999
DOI: 10.1088/0953-8984/11/32/315
|View full text |Cite
|
Sign up to set email alerts
|

Electron trapping centres and cross sections in LiNbO3studied by57Co Mössbauer emission spectroscopy

Abstract: Fast electron trapping processes and aliovalent charge states following the 57Co(EC)57Fe decay are studied in undoped, 5.4 mol% Mg-doped and 0.1 mol% Fe-doped LiNbO3 in various thermochemical reduction (TCR) states. Static 57Co Mössbauer emission spectra of congruent Mg:LiNbO3 recorded at T = 4.2 K in external magnetic field of 4.6 T are presented. Trapping cross section ratios are derived for Fe3+Li, Nb5+Li and Mg2+Li. A method to determine trap concentrations for TCR states of LiNbO3 is outlined. The electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Additional Mössbauer studies addressed the electron trapping in congruent, nearstoichiometric, Mg-doped and Fe-doped LN [210,211]. It was found that the electron trapping effect by Nb-antisite outweighs that attributed to Fe 3+ despite the larger cross section of the latter.…”
Section: Dopants To Enhance Photorefractive Damagementioning
confidence: 99%
“…Additional Mössbauer studies addressed the electron trapping in congruent, nearstoichiometric, Mg-doped and Fe-doped LN [210,211]. It was found that the electron trapping effect by Nb-antisite outweighs that attributed to Fe 3+ despite the larger cross section of the latter.…”
Section: Dopants To Enhance Photorefractive Damagementioning
confidence: 99%